Luxurious Nitrogen Fertilization of Two Sugar Cane Genotypes Contrasting for Lignin Composition Causes Changes in the Stem Proteome Related to Carbon, Nitrogen, and Oxidant Metabolism but Does Not Alter Lignin Content - Salvato, Fernanda; Wilson, Rashaun; Portilla Llerena, Juan Pablo; Kiyota, Eduardo; Reis, Karina Lima; Boaretto, Luis Felipe; Balbuena, Tiago S. [UNESP]; Azevedo, Ricardo A.; Thelen, Jay J.; Mazzafera, Paulo (Amer Chemical Soc, 2017)
Sugar cane is an important crop for sugar and biofuel production. Its lignocellulosic biomass represents a promising option as feedstock for second-generation ethanol production. Nitrogen fertilization can affect differently tissues and its biopolymers, including the cell-wall polysaccharides and lignin. Lignin content and composition are the most important factors associated with biomass recalcitrance to convert cell-wall polysaccharides into fermentable sugars. Thus it is important to understand the metabolic relationship between nitrogen fertilization and lignin in this feedstock. In this study, a large-scale proteomics approach based on GeLC-MS/MS was employed to identify and relatively quantify proteins differently accumulated in two contrasting genotypes for lignin composition after excessive nitrogen fertilization. From the similar to 1000 nonredundant proteins identified, 28 and 177 were differentially accumulated in response to nitrogen from IACSP04-065 and IACSP04-627 lines, respectively. These proteins were associated with several functional categories, including carbon metabolism, amino acid metabolism, protein turnover, and oxidative stress. Although nitrogen fertilization has not changed lignin content, phenolic acids and lignin composition were changed in both species but not in the same way. Sucrose and reducing sugars increased in plants of the genotype IACSP04-065 receiving nitrogen.
Keywords: Saccharum officinarum; cell wall; lignocellulosic ethanol; lignin; proteomics